Towards an intelligent public spending: The quality of public spending and some reflections for an Ecuador in crisis - Moncayo, Guido Andrés; Salinas, Victor Manuel (SATHIRI, 2019)
The present article was based on the hypothesis that although Ecuador, so far in the new century, has advanced socioeconomically in an important way, in recent years this growth has been reduced, and one of the explanations of this decrease is the inefficient public spending. In order to argue this statement, the document was made under a mixed methodology (qualitative-quantitative) and a comparative analytical design, for which a series of secondary data were taken that were analyzed in the light of whether they are reflecting an intelligent expense or not in the country. Prior to this point, in the first section, a brief tour of the history of public administration and its search for efficiency was made and, in the second, some of the relevant aspects that the current situation in the region leaves us Regarding the efficient use of public spending, highlighting that the 21st century began with an economic boost that in recent years has been weakened, which makes efficient spending of public resources preponderant. The elaboration of this article had as main difficulty the unavailability of more recent information, on the one hand, and on the other hand of information disaggregated at least at the provincial level, to analyze what the situation in the territory is.